Evaluation of thermal and mechanical properties of ZnSO4-B2O3-P2O5-Ho2O3 glass-ceramics - Areej S. Alqarni; Ibrahim Bulus (Química Nova)
In this study, a novel glass-ceramic (GC) obtained from ZnSO4-B2O3-P2O5-Ho2O3 composition, coded as H0.0, H0.5 and H0.8, was synthesized via molten-solidified approach. The effect of varying content of Ho2O3 from 0.5 to 0.8 mol% on thermal and mechanical properties of the prepared GC were experimentally and theoretically scrutinized. The attained results showed that inclusion of Ho2O3 content amplified crystallite size from 42.3 to 50.5 mm. Besides, the values of elastic moduli (Youngs’s, bulk, shear and longitudinal) computed via Makishima-Mackenzie’s (MM) model were slightly augmented. Finally, the decent value of thermal stability (> 150 °C) and high fracture toughness of > 20000 MPa mm1/2 achieved for the newly fabricated GC may be applicable in protective covers of portable electronics.